Understanding of the influence of PVDF polymorphism on cell behaviour - Teow, Kai Soon. (2012)
Poly(vinylidene fluoride) (PVDF) is well known as its excellent electroactive properties (piezo-, pyro- and ferroelecticity), especially β crystalline phase. Also, PVDF is a good candidate of biomaterial as its high biocompatibility. These two valuable properties make PVDF getting highly attention from scientific community. However, the knowledge of cellular response against the phase transformation of PVDF is very limited. This is the driving force of this project. In this study, solvent casting was the main approach of fabricating PVDF films as dimethylformamide was chosen as solvent used. The mechanisms and trends of transformation between α- and β-PVDF were investigated by several characterization techniques, XRD, FTIR, DSC and SEM. Alternating of the crystallization temperature was selected as the method to trigger phase transformation. A trend of β-phase formation with lowering temperature was observed. Hence, the interaction between crystalline phase and cellular behavior was observed by cell-cultured of α-rich and β-rich PVDF films.